Role of bioactive compounds in the treatment of hepatitis: A review - Roy, Arpita; Roy, Madhura; Gacem, Amel; Datta, Shreeja; Zeyaullah, Md.; Muzammil, Khursheed; Farghaly, Thoraya A.; Abdellattif, Magda H.; Yadav, Krishna Kumar; Simal-Gandara, Jesus (Frontiers in Pharmacology, 2022)
Hepatitis causes liver infection leading to inflammation that is swelling of the liver. They are of various types and detrimental to human beings. Natural products have recently been used to develop antiviral drugs against severe viral infections like viral hepatitis. They are usually extracted from herbs or plants and animals. The naturally derived compounds have demonstrated significant antiviral effects against the hepatitis virus and they interfere with different stages of the life cycle of the virus, viral release, replication, and its host-specific interactions. Antiviral activities have been demonstrated by natural products such as phenylpropanoids, flavonoids, xanthones, anthraquinones, terpenoids, alkaloids, aromatics, etc., against hepatitis B and hepatitis C viruses. The recent studies conducted to understand the viral hepatitis life cycle, more effective naturally derived drugs are being produced with a promising future for the treatment of the infection. This review emphasizes the current strategies for treating hepatitis, their shortcomings, the properties of natural products and their numerous types, clinical trials, and future prospects as potential drugs.